4D Printed Shape Morphing Biocompatible Materials Based on Anisotropic Ferromagnetic Nanoparticles (Adv. Funct. Mater. 50/2022). (9th December 2022) - Kuhnt, Tobias; Camarero‐Espinosa, Sandra; Takhsha Ghahfarokhi, Milad; Arreguín, Mariana; Cabassi, Riccardo; Albertini, Franca; Nieto, Daniel; Baker, Matthew B.; Moroni, Lorenzo
Abstract : 4D Printed Shape‐Morphing Biocompatible Materials with Unpaired Movements 4D printed shape‐morphing materials allow for remote and reversible actuation of pre‐defined structures. In article number 2202539, Lorenzo Moroni and co‐workers demonstrate that these reversible actuation can be programed to display patterns of attraction and repulsion within same object while using composites based on biocompatible anisotropic nanomagnets.